Risk of non-compliance and its impact on the profitability of Islamic banks: (Applied res earch in the Islamic Cooperation Bank)For the years (2016-2012) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research deals with the risks of non-compliance and its impact on the profitability of Islamic banks. Research variables were measured and analyzed as the risk of non-compliance as an independent variableand profitability as a dependent variable. The profitability was measured by three indicators ((rate of return on assets, rate of return on equity and rate of return on Total deposits)) The results of the research showed a significant relationship between the risk of non-compliance and the rate of return on assets and rate of return on total deposits, while there was no relationship between the risk of non-compliance and rate of return on ownership. The research recommended that the senior management of the Islamic Investment Bank should work to find the appropriate outlets to enhance the banking return by attracting bank deposits and directing investments towards investment channels that are compatible with the nature of Islamic banking work and working in the light of a moderate balance between liquidity, profitability and safety, On the competitive role of the bank with other competitors.